Labour market participation of refugees and asylum seekers in Brussels: innovation and institutional complementarity - Adèle Garnier; Annaelle Piva (Brussels Studies)
Following the arrival of many asylum seekers in 2015-2016, the participation of asylum seekers and refugees in the labour market has become a major political concern. In Brussels, this issue is part of a context of structural unemployment affecting non-European populations in particular, and of an employment support policy which is opposed to targeted measures for refugees and asylum seekers. In order to address these challenges, organisations which work to promote the participation of refugees and asylum seekers in the labour market must innovate. This article focuses on four recent initiatives and how they fit into pre-existing institutional dynamics, in order to provide an analysis which complements the literature on the “Brussels institutional puzzle”.